Plight of the Fortune Tellers : Why We Need to Manage Financial Risk Differently - Rebonato, Riccardo (Book collections on Project MUSE., 2010)
Today's top financial professionals have come to rely on ever-more sophisticated mathematics in their attempts to come to grips with financial risk. But this excessive reliance on quantitative precision is misleading--and puts everyone at risk. In Plight of the Fortune Tellers, Riccardo Rebonato forcefully argues that we must restore genuine decision making to our financial planning. Presenting a financial model that uses probability, experimental psychology, and decision theory, Rebonato challenges us to rethink the standard wisdom about risk management. He offers a radical yet surprisingly c.